(untitled) (Boulder, Colorado, 2020)
Explores Japan's historical narratives, and their impact on both domestic politics and diplomatic relations, as they have evolved from 1946 to the present
Keywords: Nhật Bản,Japan; Ngoại giao,Foreign relations